2010
DOI: 10.1007/s00384-010-1049-8
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus and colorectal cancer: evidences and pitfalls of published literature

Abstract: HPV has been detected in the majority of reported series, but published literature lacks in definitive data regarding standard methods of investigation and stratification of groups and population. These data encourage further studies with the aim to investigate the presence of the virus in larger series, its possible role in oncogenesis, the integration in host genome, the expression of viral oncoproteins, the mutations in HPV positive cancers and routes of colon infection (hematologic/lymphatic spreading or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
0
11

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 22 publications
2
41
0
11
Order By: Relevance
“…Although several investigators have found an association between HPV and colorectal carcinoma, [54][55][56] the role of HPV in carcinogenesis of the colon remains to be elucidated. 57 Morphologically, low-grade and high-grade HPVrelated squamous mucosal lesions are similar whether they occur in the anus or cervix. Their morphologic similarities far outweigh their differences, both cytologically and histologically, as seen in Figures 5 and 6.…”
Section: Histology Of Ain and Anal Cancermentioning
confidence: 99%
“…Although several investigators have found an association between HPV and colorectal carcinoma, [54][55][56] the role of HPV in carcinogenesis of the colon remains to be elucidated. 57 Morphologically, low-grade and high-grade HPVrelated squamous mucosal lesions are similar whether they occur in the anus or cervix. Their morphologic similarities far outweigh their differences, both cytologically and histologically, as seen in Figures 5 and 6.…”
Section: Histology Of Ain and Anal Cancermentioning
confidence: 99%
“…Therefore, several recent studies including one from our group pointed-out that high-risk HPVs are present in human CRCs, specifically types 16, 18, 31, 33, and 35 [7,12,15,16,52]. Moreover, six recent meta-analysis studies confirmed the presence of high-risk HPVs in human CRCs [70,[91][92][93][94][95]; however, the prevalence of high-risk HPVs varied from one geographic location to another [7,52]. Meanwhile, it was stated that high-risk HPVs are present especially in the invasive form of these malignancies worldwide [15].…”
Section: High-risk Hpvs In Colorectal Cancersmentioning
confidence: 96%
“…Nos últimos anos, entretanto, artigos da literatura especializada vêm mostrando a presença do DNA do HPV em amostras de tecido de carcinomas do esôfa-go 13 , estômago 14,15 , pulmão 14 , mama 16 e colorretal [17][18][19] . O HPV foi detectado em até 37,5% dos adenocarcinomas gástricos 15 , e em 27,8% dos CEC esofágicos 20 , havendo diferença em áreas de alta e de baixa prevalência para esse tumor maligno (65 e 6%, respectivamente) 21 .…”
unclassified
“…O HPV foi detectado em 51,4% dos CEC e em 16,2% dos adenocarcinomas do pulmão, sendo que o risco de CEC pulmonar é 3,5 vezes maior em doentes contaminados pelo HPV 23 , embora, outros neguem essa associação 24 . O HPV foi encontrado entre 41,7 e 82,1% dos adenocarcinomas do cólon 17,[25][26][27] , o que não foi observado por outros autores 28 . Outro estudo revelou os tipos 16 e 18 do HPV em 67% dos carcinomas e em 56% dos adenomas do cólon e em 28% das vezes na mucosa normal 25 .…”
unclassified
See 1 more Smart Citation